Implementation Of Islamic Dawah Through Islamic Music Art Hadroh To Students Of The Malaysian Civilization Guidance Students, Selangor Malaysia - Diyan Yusri; Usmaidar Usmaidar; Anjur Perkasa Alam; Tuti Rezeki Awaliyah Siregar; M.Baihaqi Zailani; Ahmad Syahroni (International Journal of Science Education and Cultural Studies, 2025)
This research serves to explore the implementation of Islamic da'wah through Hadroh among students at Sanggar Bimbingan Peradaban Malaysia. To make music, practices of participation observation, in-depth interviews, and document analysis were used as a case study. Findings have shown that Hadroh increases students' drive to understand Islam, reinforces their religious convictions, and makes it more likely that they would get involved in Islamic activities. Musical practice combined with lyrical interpretation and community participation gives students an overall learning experience. After evaluating existing educational resources, the study concluded that Hadroh was an effective tool for Islamic da'wah. And it was especially so among younger audiences. This study makes a concrete contribution to Islamic education by showing how artistic products can in fact be part of religious study and greatly enhance understanding. Future research remains to be done. What is needed is to try whether Islamic music and da'wah continue in the long-term to have an effect